Evaluation of chromogenic selective agar (CHROMagar STEC) for the direct detection of Shiga toxin-producing Escherichia coli from faecal specimens. Issue 3 (14th January 2020) - Jenkins, Claire; Perry, Neil T.; Godbole, Gauri; Gharbia, Saheer
Abstract : Shiga toxin-producing Escherichia coli (STEC) are zoonotic pathogens that cause symptoms of severe gastrointestinal disease, including haemolytic uraemic syndrome (HUS), in humans. Currently in England, STEC serotypes other than O157:H7 are not cultured at the local hospital laboratories. The aim of this study was to evaluate the utility of CHROMagar STEC for the direct detection of STEC from faecal specimens in a diagnostic setting, compared to the current reference laboratory method using PCR targeting the Shiga-toxin gene ( stx ) to test multiple colonies cultured on MacConkey agar. Of the 292 consecutive faecal specimens submitted to the Gastrointestinal Bacterial Reference Unit that tested positive for stx by PCR, STEC could not be cultured on MacConkey agar or CHROMagar STEC from 87/292 (29.8 %). Of the 205 that were cultured, 106 (51.7 %) were detected on both MacConkey agar and CHROMagar STEC and 99 (48.3 %) were detected on MacConkey agar only. All 106 (100 %) isolates that grew on CHROMagar STEC had the ter gene cassette, known to be associated with resistance to tellurite, compared to 13/99 (13.1 %) that were not detected on CHROMagar STEC. CHROMagar STEC supported the growth of 36/40 (90 %) isolates harbouring stx2a or stx2d, the subtypes most frequently associated with progression to HUS. Of the 92 isolates harbouring eae, an important STEC virulence marker, 77 (83.7 %) grew on CHROMagar STEC. CHROMagar STEC is a useful selective media for the rapid, near-patient detection of STEC that have the potential to cause HUS.